OC-013 INDIVIDUAL STRATEGY FOR PATIENTS WITH ABDOMINAL WALL EVENTRATION – DIFFERENT COMPONENTS SEPARATION TECHNIQUE WITH MESH AUGMENTATION. (13th October 2022) - Zuvela, M; Bogdanovic, A; Galun, D; Palibrk, I; Velickovic, J; Djukanovic, M; Bidzic, N; Zivanovic, M; Zuvela, M; Zuvela, M
Abstract: Aim: To present individual approach for patients with abdominal wall eventration using various anterior component separation techniques (aCST) with mesh augmentation. Materials and Methods: Between January 2008 and April 2022, 194 patients with abdominal wall eventration underwent surgery by single surgeon. Surgical treatment consists: a) enlargement of the abdominal cavity using different aCST (Ramirez CST, modified CST in the presence of enterostomies, "open book" modification CST, "method of wide myofascial release" or combination of these techniques); b) mesh augmentation (sublay or onlay hernioplasty); c) prolonged muscle relaxation and mechanical respiratory support in intensive care unit. Results: Type of abdominal wall reconstruction: 143 Ramirez CST, 35 modification CST in the presence of enterostomies, 11"open book" CST modification, 5 "method of wide myofascial release", 159 onlay mesh hernioplasty and 35 sublay mesh hernioplasty. Mean hernia defect size was 255 cm 2 (100–750). During the mean follow-up of 31 months, 78 (40%) patients had one or more complications: intraabdominal hypertension 8 (4, 1%), seroma 13 (6, 7%), hematoma 10 (5, 1%), wound/mesh infections 21 (10, 8%), skin necrosis 40 (20, 6%), pain 3 (1, 6%), and recurrence 5 (2, 6%). There were 10 (5, 1%) postoperative deaths. The cause of dead was significant comorbidity in 8 patients and postoperative compartment syndrome in two. Conclusion: Eventration disease is a complex surgical problem and its treatment is associated with significant complications. Individual strategy for each patient based on multidisciplinary approach using different component separation techniques with mesh augmentation may improve postoperative results.